Neuropharmacology of Fisetin as a Senotherapeutic Agent: Investigating Its Role in Neurodegeneration and Brain Aging: Fisetin in Neurodegeneration and Aging - Javaid, Sidra; Memon, Abeer; Anwar, Binish; Bader, Zarafshan; Aftab, Ayesha; Perveen, Fouzia; Haq, Ehsan Ul (Pakistan Journal of Health Sciences, 2024)
Fisetin, a flavonoid in various fruits and vegetables, has emerged as a promising chemotherapeutic agent with potential neuroprotective effects, particularly in neurodegeneration and brain aging. Objective: To explore the role of fisetin in mitigating age-related neuronal damage by targeting oxidative stress, inflammation, and cellular senescence, common contributors to neurodegenerative diseases such as Alzheimer’s and Parkinson’s. Methods: Following PRISMA guidelines, relevant studies were sourced from ScienceDirect, Google Scholar, and PubMed, spanning publications between April 2014 and August 2024. One website was also used to retrieve studies, i.e., Frontiers. Fisetin’s mechanism of action includes modulating key pathways, such as the inhibition of inflammatory markers, reduction of Reactive Oxygen Species (ROS), and protection against neuronal apoptosis. Results: Studies conducted on various animal models and human-derived neurodegenerative cell lines reveal its potential to improve cognitive function and reduce the progression of age-related brain disorders. Conclusions: Fisetin’s ability to selectively target senescent cells, reduce neuroinflammation, and enhance synaptic function positions it as a potential therapeutic for brain aging. Future research focusing on clinical trials and dosing optimization was crucial to establishing fisetin as a viable treatment for neurodegenerative conditions and cognitive decline associated with aging.